Charakterystyka i cechy diagnostyczne wciornastków z rodziny Thripidae (Insecta, Thysanoptera) najczęściej występujących w koronach drzew lasów centralnej Europy - Kucharczyk, Halina; Kucharczyk, Marek (Leśne Prace Badawcze, 2013)
The paper presents characteristic and morphological diagnostic features of females and second larval instar of six terebrantian species: Oxythrips ajuga e Uzel 1895, O. bicolor (O. M. Reuter 1879), Taeniothrips inconsequens (Uzel 1895), Thrips calcaratus Uzel 1895, T. minutissimus Linnaeus 1758 and T. pini (Uzel 1895). The species are the most numerously and frequently caught in traps in the canopy layer of various Central European forests. Both adults and larvae of Oxythrips spp. may be easily recognized by features present at the end of their abdomen: the former by length of the abdominal segment X; the latter by differences in the length and position of spines. Adults of other the species mentioned above differ in the following features: number of antennal segments, number of setae in the distal part of their first pair of wings, presence or absence of additional setae on abdominal sternites and pleurites, presence or absence of a tooth on the tarsus of the first pair of legs. The main features differentiating larvae of these species (besides T. pini larva which have been hitherto undescribed) are body sclerotisation and length, and shape of the comb surrounding the IXth abdominal segment.